Whittington - Armstrong, Alan W., 1939-; Schindler, S. D. (New York : Yearling, 2006)
Whittington, a feline descendant of Dick Whittington$1 (Bs famous cat of English folklore, appears at a rundown barnyard plagued by rats and restores harmony while telling his ancestor$1 (Bs story.s
Includes bibliographical references (p. 187-191).
Keywords: Whittington, Richard, -- d. 1423 -- Legends -- Juvenile fiction; Whittington, Richard, -- d. 1423 -- Legends -- Fiction; Cats -- Juvenile fiction; Cats -- Fiction; Domestic animals -- Fiction